HISTORICAL STUDY OF INDIAN CULTURE OF THE GUPTA PERIOD - Pathak, Poonam; Parveen, Shagufta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Gupta period is like a star in the history of Indian culture. In this era, Indian civilization and culture had reached the pinnacle of its development. Be it society, politics, literature, art or religion, extraordinary progress was made in all the fields during the Gupta period. Historians call the Gupta period, in which the movement of renaissance reached the pinnacle of development by achieving many successful achievements in the field of literature and art, the golden age of Hindu religion and the period of Hindu renaissance. The founder of this dynasty was Chandragupta I, after him his son Samudragupta extended the boundaries of the empire far and wide through his glorious victories. After this, the most important ruler of the Gupta era, Chandragupta Vikramaditya ascended the throne, who on one hand expanded the empire through his extraordinary strength, valour and leadership skills, and on the other hand gained popularity among the people through efficient administration and religious tolerance. Skandagupta was the last glorious king of this golden age, whose glory shone on the whole of northern India. These rulers patronised art and literature during their rule and took all social, economic and administrative fields to the pinnacle of progress.